Coherent integration algorithm for random pulse repetition interval radar based on iterative adaptive approach. Issue 22 (25th September 2020) - Yu, Wenchao; Su, Weimin; Gu, Hong; Yang, Jianchao; Lu, Xingyu
Abstract : An iterative adaptive approach (IAA) based algorithm is presented to realise coherent integration for the random pulse repetition interval radar. The proposed method firstly removes the effect of Doppler ambiguity via phase compensation, and then accomplishes target focusing via conducting the azimuth IAA and range inverse fast Fourier transform. Theoretical analysis and numerical experiments have verified the effectiveness of the proposed method.